Autophagy in the presynaptic compartment. (August 2018) - Lüningschrör, Patrick; Sendtner, Michael
Highlights: In neurons, most autophagosomes form in axon terminals. In neurons, autophagy is involved in quality control of synaptic components. Distinct synaptic proteins interact with the autophagy machinery. Autophagy of synaptic components could function in regulation of synaptic plasticity. Abstract : Regulated release of neurotransmitter depends on the orchestrated function of a large number of proteins in the presynaptic compartment. When synaptic vesicles fuse with the plasma membrane, these membranes and the attached proteins are endocytosed and either recycled or degraded. This turnover needs to be tightly regulated in a timely and spatially confined manner. Increasing evidence suggests that these mechanisms do not only serve for the removal of defective synaptic vesicles or structural proteins of the active zone but also contribute to pathways regulating synaptic strength. The corresponding presynaptic autophagy system thus appears also important for synaptic maintenance and plasticity. Exciting new studies provide evidence how the autophagy machinery recognizes and degrades synaptic components and lay the ground to understand how autophagy in the presynaptic compartment contributes to modulation and maintenance of synaptic function.